Poly(methylhydrosiloxane) as a reductant in the catalytic base-free Wittig reaction - Tönjes, Jan; Longwitz, Lars; Werner, Thomas (Green Chemistry)
PMHS proved to be a suitable terminal reductant for P(iii)/P(v) redox cycling with a methyl-substituted phosphetane as catalyst and BuOAc as solvent. The formation of water by silanol condensation was identified as main pathway of siloxane formation.
Keywords: T2; CSSD

Stereoselective Synthesis of acis-Cedrane-8,9-diol as a Key Intermediate for an Amber Odorant - Stefanow, Vivian; Grandane, Aiga; Eh, Marcus; Panten, Johannes; Spannenberg, Anke; Werner, Thomas (Organic Process Research & Development)
Keywords: T4; CSSD

Stereoselective Synthesis of acis-Cedrane-8,9-diol as a Key Intermediate for an Amber Odorant - Stefanow, Vivian; Grandane, Aiga; Eh, Marcus; Panten, Johannes; Spannenberg, Anke; Werner, Thomas (Organic Process Research & Development)
Keywords: T4; CSSD

AMPA-15N – Synthesis and application as standard compound in traceable degradation studies of glyphosate - Wirth, Marisa A.; Longwitz, Lars; Kanwischer, Marion; Gros, Peter; Leinweber, Peter; Werner, Thomas (Ecotoxicology and Environmental Safety)
Keywords: T4; CSSD

Selective Construction of C−C and C=C Bonds by Manganese Catalyzed Coupling of Alcohols with Phosphorus Ylides - Liu, Xin; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: T1; T3; CSSD

Relationierung von Theorie und Praxis in der Lehrkräftebildung im Fach Physik – eine Übersicht über Forschungen und Formate - Vogelsang, Christoph; Rehfeldt, Daniel (Edition Fachdidaktiken)
Auch in der Lehrkräftebildung in der Domäne Physik ist es Ziel, im Studium vermittelte, theoretische Kenntnisse mit berufspraktischen Anforderungen von angehenden Lehrkräften in Beziehung zu setzen. Charakteristisch für das Fach ist dabei zum einen eine eher anwendungsorientierte theoretische Position zum Zusammenhang von Theorie und Praxis. Zum anderen zeichnet es sich auch durch eine Art experimentelle Orientierung aus, die die Relationierung beider Aspekte als empirisch zu klärende Herausforderung begreift. In diesem Beitrag wird daher zunächst ein kurzer Überblick über Modelle und empirische Forschungen zum Zusammenhang zwischen theoretischem Wissen und praktischem Lehrkräftehandeln gegeben, die das Verständnis der Relationierung von Theorie und Praxis in der Didaktik der Physik prägen. Anschließend werden typische Lehr-Lern-Formate beschrieben und dabei auch jeweils die Ergebnisse begleitender Wirksamkeitsevaluationen kurz dargestellt.

Exploring the impact of pre-service science teachers’ reflection skills on the development of professional knowledge during a field experience - Kulgemeyer, Christoph; Kempin, Maren; Weißbach, Anna; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (International Journal of Science Education)
Keywords: Education

Entwicklung der Fähigkeit zur Unterrichtsplanung im Fach Physik - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020)

Design Strategies for Electrocatalysts from an Electrochemist’s Perspective - Linnemann, Julia; Kanokkanchana, Kannasoot; Tschulik, Kristina (ACS Catalysis)
The aim to produce highly active, selective, and long-lived electrocatalysts by design drives major research efforts toward gaining fundamental understanding of the relationship between material properties and their catalytic performance. Surface characterization tools enable to assess atomic scale information on the complexity of electrocatalyst materials. Advancing electrochemical methodologies to adequately characterize such systems was less of a research focus point. In this Review, we shed light on the ability to gain fundamental insights into electrocatalysis from a complementary perspective and establish corresponding design strategies. These may rely on adopting the perceptions and models of other subareas of electrochemistry, such as corrosion, battery research, or electrodeposition. Concepts on how to account for and improve mass transport, manage gas bubble release, or exploit magnetic fields are highlighted in this respect. Particular attention is paid to deriving design strategies for nanoelectrocatalysts, which is often impeded, as structural and physical material properties are buried in electrochemical data of whole electrodes or even devices. Thus, a second major approach focuses on overcoming this difference in the considered level of complexity by methods of single-entity electrochemistry. The gained understanding of intrinsic catalyst performance may allow to rationally advance design concepts with increased complexity, such as three-dimensional electrode architectures. Many materials undergo structural changes upon formation of the working catalyst. Accordingly, developing “precatalysts” with low hindrance of the electrochemical transformation to the active catalyst is suggested as a final design strategy.
Keywords: electrocatalysis

Unexpectedly High Capacitance of the Metal Nanoparticle/Water Interface: Molecular‐Level Insights into the Electrical Double Layer - Azimzadeh Sani, Mahnaz; Pavlopoulos, Nicholas G.; Pezzotti, Simone; Serva, Alessandra; Cignoni, Paolo; Linnemann, Julia; Salanne, Mathieu; Gaigeot, Marie‐Pierre; Tschulik, Kristina (Angewandte Chemie International Edition)
The electrical double‐layer plays a key role in important interfacial electrochemical processes from catalysis to energy storage and corrosion. Therefore, understanding its structure is crucial for the progress of sustainable technologies. We extract new physico‐chemical information on the capacitance and structure of the electrical double‐layer of platinum and gold nanoparticles at the molecular level, employing single nanoparticle electrochemistry. The charge storage ability of the solid/liquid interface is larger by one order‐of‐magnitude than predicted by the traditional mean‐field models of the double‐layer such as the Gouy–Chapman–Stern model. Performing molecular dynamics simulations, we investigate the possible relationship between the measured high capacitance and adsorption strength of the water adlayer formed at the metal surface. These insights may launch the active tuning of solid–solvent and solvent–solvent interactions as an innovative design strategy to transform energy technologies towards superior performance and sustainability.
Keywords: single-entity electrochemistry; electrical double layer; supercapacitor; nanoparticles

Single Co3O4 Nanocubes Electrocatalyzing the Oxygen Evolution Reaction: Nano-Impact Insights into Intrinsic Activity and Support Effects - Liu, Zhibin; Corva, Manuel; Amin, Hatem M. A.; Blanc, Niclas; Linnemann, Julia; Tschulik, Kristina (International Journal of Molecular Sciences)
Single-entity electrochemistry allows for assessing electrocatalytic activities of individual material entities such as nanoparticles (NPs). Thus, it becomes possible to consider intrinsic electrochemical properties of nanocatalysts when researching how activity relates to physical and structural material properties. Conversely, conventional electrochemical techniques provide a normalized sum current referring to a huge ensemble of NPs constituting, along with additives (e.g., binders), a complete catalyst-coated electrode. Accordingly, recording electrocatalytic responses of single NPs avoids interferences of ensemble effects and reduces the complexity of electrocatalytic processes, thus enabling detailed description and modelling. Herein, we present insights into the oxygen evolution catalysis at individual cubic Co3O4 NPs impacting microelectrodes of different support materials. Simulating diffusion at supported nanocubes, measured step current signals can be analyzed, providing edge lengths, corresponding size distributions, and interference-free turnover frequencies. The provided nano-impact investigation of (electro-)catalyst-support effects contradicts assumptions on a low number of highly active sites.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; single-entity electrochemistry

Förderung angehender Lehrkräfte im Umgang mit Evidenzen für den naturwissenschaftlichen Unterricht - Pollmeier, Pascal; Fechner, Sabine (Lehrkräftebildung neu gedacht. Ein Praxishandbuch für die Lehre in den Naturwissenschaften und deren Didaktiken)

Zwischen den Stühlen? – Verknüpfung von Erfahrungen des Praxissemesters mit Theorien im Lehramtsstudium Chemie. Sukzessiven Kompetenzaufbau nach dem Praxissemester gestalten - Pollmeier, Pascal; Fechner, Sabine (Theorie und Praxis in der Lehrerbildung - Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

Laborpraktika auf Distanz. Ansätze in den Naturwissenschaften - Bauer, Anna; Sacher, Marc; Habig, Sebastian; Fechner, Sabine (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre)

Effect of Oxygen-Donor Charge on Adjacent Nitrogen-Donor Interactions in Eu3+ Complexes of Mixed N,O-Donor Ligands Demonstrated on a 10-Fold [Eu(TPAMEN)]3+ Chelate Complex - Schnaars, Kathleen; Kaneko, Masashi; Fujisawa, Kiyoshi (Inorganic Chemistry)
To reduce high-level radiotoxic waste generated by nuclear power plants, highly selective separation agents for minor actinides are mandatory. The mixed N,O-donor ligand N,N,N′,N′-tetrakis[(6-carboxypyridin-2-yl)methyl]ethylenediamine (H4TPAEN; 1) has shown good performance as a masking agent in Am3+/Eu3+ separation studies. Adjustments on the pyridyl backbone to raise the hydrophilicity led to a decrease in selectivity and a decrease in M3+–Nam interactions. An enhanced basicity of the pyridyl N-donors was given as a cause. In this work, we examine whether a decrease in O-donor basicity can promote the M3+–Nam interactions. Therefore, we replace the deprotonated “charged” carboxylic acid groups of TPAEN4– by neutral amide groups and introduce N,N,N′,N’-tetrakis[(6-N″,N′′-diethylcarbamoylpyridin-2-yl)methyl]ethylenediamine (TPAMEN; 2) as a new ligand. TPAMEN was crystallized with Eu(OTf)3 and Eu(NO3)3·6H2O to form positively charged 1:1 [Eu(TPAMEN)]3+ complexes in the solid state. Alterations in the M–O/N bond distances are compared to [Eu(TPAEN)]− and investigated by DFT calculations to expose the differences in charge/energy density distributions at europium(III) and the donor functionalities of the TPAEN4– and TPAMEN. On the basis of estimations of the bond orders, atomic charges spin populations, and density of states in the Eu and potential Am and Cm complexes, the specific contributions of the donor–metal interaction are analyzed. The prediction of complex formation energy differences for the [M(TPAEN)]− and [M(TPAMEN)]3+ (M3+ = Eu3+, Am3+) complexes provide an outlook on the potential performance of TPAMEN in Am3+/Eu3+ separation.

Split-ring polariton condensates as macroscopic two-level quantum systems - Xue, Yan; Chestnov, Igor; Sedov, Evgeny; Kiktenko, Evgeniy; Fedorov, Aleksey K.; Schumacher, Stefan; Ma, Xuekai; Kavokin, Alexey (Physical Review Research)

Structuring coflowing and counterflowing currents of polariton condensates in concentric ring-shaped and elliptical potentials - Barkhausen, Franziska; Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Adatom mediated adsorption of N‐heterocyclic carbenes on Cu(111) and Au(111) - Jain, Mitisha; Gerstmann, Uwe; Schmidt, Wolf Gero; Aldahhak, Hazem (Journal of Computational Chemistry)
Keywords: Computational Mathematics; General Chemistry

Spin Polarization, Electron–Phonon Coupling, and Zero-Phonon Line of the NV Center in 3C-SiC - Jurgen von Bardeleben, Hans; Cantin, Jean-Louis; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Hyperfine and nuclear quadrupole splitting of the NV− ground state in 4H-SiC - Murzakhanov, F. F.; Yavkin, B. V.; Mamin, G. V.; Orlinskii, S. B.; von Bardeleben, H. J.; Biktagirov, Timur; Gerstmann, Uwe; Soltamov, V. A. (Physical Review B)